(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
The feed shortage is the key bottleneck of livestock production sector in Ethiopia. Ever green fodder of trees and shrubs in agroforestry systems provides an alternative solution to boost availability of feed throughout the year. The paper was reviewed leaf biomass yield and chemical composition of major fodder trees and shrubs in agroforestry systems across different agroecologies in Ethiopia. Biomass DM yields of indigenous fodder trees were significantly different (p < 0.05) across agroecologies. In the highlands, biomass yield/ha was greatest (p < 0.05) for E. brucei followed by H. abyssinica and V. amygdalina while the lowest was for A. alpine. In the midland, D. steudneri had the highest (p=0.001) biomass yield/tree while the least was observed in M. ferruginea and V. amygdalina. The highest biomass yield in the lowland was for C. africana and E. racemose. In general, the average DM biomass yields were 0.22- 15.43, 0.28–23.1 and 10.81 –54.1 kg DM/tree for highland, midland and lowland, respectively. Erythrina brucei, Dracaena steudneri and Cordia africana had the highest biomass yield in highland, midland and lowland, respectively (p < 0.05). There were significant differences in chemical composition among the fodder tree and shrub species. Chemical composition of the fodder species had on average 89.63 % Dry matter, 21.7 % Crud protein, 66.56 % Digestible dry matter, 52.95 % Neutral detergent fibber, 28.66 % Acid detergent fibber, 11.57 % Acid detergent lignin, 4.17 % Ether extract, 7.49 % Ash, 24.28 Hemicelluloses and 17.09 cellulose. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 283-294